The Use of Social Media in Searching for Information about Papua - Ashrianto, Panji Dwi; Yustitia, Senja (Universitas Semarang, 2020)
The use of social media in searching for information relating to political issues has become immensely crucial since in those domains the information appearing is often biased and dominated by certain parties or groups. One of the political information that has frequently emerged in Indonesia is about Papua. The significance of this research because Papua is a crucial problem in Indonesian history, and its conversation has continued, especially in social media. This study intends to examine the use of social media in searching for information about Papua. That is a novelty of research because no one has examined Papua in terms of the use of social media. The Uses and Gratification Theory is used in the study with a mixed method approach as both quantitative and qualitative data were concurrently utilized. Quantitative data obtained from a questionnaire distributed to 100 UPN